Gait speed, balance and functional capacity in a sample of community-dwelling older adults - Galán-Mercant, Alejandro (2017)
Introduction: Falls in older people is an important public health concern since they are responsible for a high number of hospitalizations, health complications, disability, and death. Gait speed has been identified as a predictor of health state in elderly populations and it is related to falls and functional capacity. The aim of this study was to identify the risk of falling in a sample of Portuguese older adults living in the community and to investigate the associations between gait speed, balance, and functionality. Methods: This was a cross-sectional study. Assessment included gait speed (GS) with 4-meter walk test; balance with the Berg Balance Scale (BBS); functional capacity with the Composite Physical Function Scale (CPF). Descriptive and correlational statistics were performed to analyze data. Results: 46 community-dwelling older adults (32 women; 14 men) aged 77 ± 9 years participated in our study. Mean value for GS was 1.17 ± 0.37 m/s which is normal for this population. For BBS and CPF median was 52 and 19, respectively. BBS results revealed a risk of falling off 43% and functional capacity of our participants was at moderate levels. The study of correlations between variables also showed positive associations between GS and BBS (R = 0.631; p = 0.00) and between GS and CPF (R = 0.605; p = 0.00). Conclusions: Positive associations between GS and balance and between GS and functional capacity highlight the role of GS in the assessment of fall risk and functional capacity since it is a simple and easy test to perform.